Letter from Carl D. Duncan to Patricia Whiting, March 22, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan expresses concern for Whiting's ill sister and describes a workshop session presented by Buckminster Fuller.